The role of material efficiency to reduce CO2 emissions during ship manufacture: A life cycle approach. (January 2017) - Gilbert, P.; Wilson, P.; Walsh, C.; Hodgson, P.
Abstract: Low carbon shipping research focuses on energy efficiency and mitigation measures related to operations and technology. However, reducing energy use and greenhouse gas emissions associated with a vessel's material production receives limited attention. Material efficiency is defined as "providing material services with less material production and processing". The current business model for ship building and breaking does not embrace fully material efficiency principles. Exploring a case study of a vessel's steel hull, this study applies a Life Cycle Assessment approach to determine the effectiveness of material efficiency to reduce CO2 emissions. When compared to Business as Usual, designing and manufacturing for 100% hull reuse provides an emissions reduction of 29% from 221, 978 t CO2 to 158, 285 t CO2 ; 50% reuse provides a 10% reduction (199, 816 t CO2 ). From a technical and safety perspective there remain key barriers that need addressing: a vessel's hull would require to be designed for dismantling to improve reuse; the operation and maintenance schedule must ensure the value of the steel is retained and; data must flow between key stakeholders on the quality of the steel. Despite these challenges, progressing material efficiency would require different business models that reach out and integrate the whole supply chain. There is a need for public and privately funded demonstration projects at a range of scales and markets, to provide investors the confidence that there is retained value in the steel hull when it reaches its end-of-life. Highlights: Low carbon emissions reduction in shipping focuses on operations and technology. Material efficiency (ME) provides material services with less material production. LCA of a steel hull used to demonstrate effectiveness of ME to reduce CO2 . 50% hull reuse provides a 10% emissions reduction compared to BAU. Barriers remain regarding business models and financial and technical feasibility.